THEORETICAL ASPECTS OF AGGRESSIVE TAX PLANNING: DOMESTIC AND EUROPEAN EXPERIENCE (INNOVATIVE ECONOMY, 2024)
Maliarchuk O.V. THEORETICAL ASPECTS OF AGGRESSIVE TAX PLANNING: DOMESTIC AND EUROPEAN EXPERIENCEPurpose. The aim of the article is a comprehensive analysis of the essence of aggressive tax planning, its legal means, determination of the limits of this planning and the development of proposals for improving the tax legislation of Ukraine taking into account the European experience.Methodology of research. The research methodology is based on the use of systematic analysis, critical analysis of scientific sources, case studies and practical examples, as well as the method of identifying patterns and interrelationships. Systematic analysis was applied to comprehensively study the essence of aggressive tax planning and its legal aspects, which allowed for the identification of the main methods and strategies used by enterprises. Critical analysis of scientific sources helped assess the effectiveness of existing regulatory measures, identify shortcomings, and substantiate proposals for their improvement. Case studies and practical examples of international corporations such as Starbucks, Apple, Amazon, and Google provided the identification of specific aggressive tax planning strategies used in practice.The method of identifying patterns and interrelationships facilitated the analysis of current trends in aggressive tax planning and the formulation of recommendations to enhance the transparency and effectiveness of tax legislation.Findings. The research identified the main methods of aggressive tax planning used by international corporations, such as transfer pricing, the use of offshore zones, and complex transaction schemes. The effectiveness of internal regulation and the European regulatory framework in countering these practices was assessed. The analysis showed that measures like the Anti-Tax Avoidance Directive (ATAD) and the BEPS Action Plan are effective tools in combating aggressive tax planning. At the same time, the need for increased transparency, improvement of national legislation, and strengthening international cooperation to reduce tax abuses was emphasized.Originality. Approaches to the regulation of aggressive tax planning, which, unlike the existing ones, include a comprehensive analysis of the methods of using offshore zones, transfer pricing and complex transaction schemes are substantiated. The developed approaches contribute to enhancing the transparency of financial operations, provide more effective prevention of tax abuses, and reduce the risks of legal consequences for enterprises. The proposed recommendations encompass the improvement of national legislation considering European experience, ensuring higher productivity and efficiency of tax control while reducing the cost of tax administration and strengthening trust in the tax system.Practical value. The obtained results can be useful for legislators, tax practitioners and other interested parties, contributing to the development of effective strategies to overcome the challenges of aggressive tax planning in a globalized economy.Key words: tax regulation, international corporations, tax obligations, corporate governance, tax planning, reporting.
Keywords: tax regulation; international corporations; tax obligations; corporate governance; tax planning; reporting.